Transportation as a Service for International Trade in Uzbekistan: an Analysis from Export and Import Development - Shahparan, Mohammad; Shakhzoda Akhmedova; Kadirova, Irina Vladimirovna (MultiTech Publisher, 2024)
Transportation is the most important part of international trade. This paper examines the role of transportation as international trade in Uzbekistan from export and import perspectives. The paper reveals the types of developed transportations in Uzbekistan for export and import business. Export and import business development depends on transportation service because of movement of products and services. The facilitation of cross-border trade in products and services is one of the major contributions of the transportation industry to Uzbekistan's economy. Proper methods and recommendations that may help for the further development of international trade trough transportation in Uzbekistan. It is essential to focus on this topic, as it offers both the necessary human mobility and distribution for production, directly connecting companies to global markets. Transport networks that are economical and efficient enhance the prospects for both individuals and enterprises to reap the benefits of globalization.